2019
DOI: 10.1093/mnras/stz3505
|View full text |Cite
|
Sign up to set email alerts
|

Effects of chaos on the detectability of stellar streams

Abstract: Observations show that stellar streams originating in satellite dwarf galaxies are frequent in the Universe. While such events are predicted by theory, it is not clear how many of the streams that are generated are washed out afterwards to the point in which it is imposible to detect them. Here we study how these diffusion times are affected by the fact that typical gravitational potentials of the host galaxies can sustain chaotic orbits. We do this by comparing the behaviour of simulated stellar streams that … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 81 publications
(82 reference statements)
0
13
0
Order By: Relevance
“…They explored different structural and kinematical properties and found that globular clusters behave similarly, independently of the presence of tidal tails or any other kind of extra-tidal feature, or the absence thereof. Recently, Mestre et al (2020) compared the behavior of simulated streams embedded in chaotic and non-chaotic regions of the phase-space. They find that typical gravitational potentials of host galaxies can sustain chaotic orbits, which in turn do reduce the time interval during which streams can be detected.…”
Section: Analysis and Discussionmentioning
confidence: 99%
“…They explored different structural and kinematical properties and found that globular clusters behave similarly, independently of the presence of tidal tails or any other kind of extra-tidal feature, or the absence thereof. Recently, Mestre et al (2020) compared the behavior of simulated streams embedded in chaotic and non-chaotic regions of the phase-space. They find that typical gravitational potentials of host galaxies can sustain chaotic orbits, which in turn do reduce the time interval during which streams can be detected.…”
Section: Analysis and Discussionmentioning
confidence: 99%
“…Chaos (or instabilities) inside the barred region may propagate over long time period and further relates with the formations of spiral arms or inner disc rings depending upon the bar strength (strong or weak) 10,25,30,33 . Now for model 1, orbits are escaping and chaotic with high MLE for initial point x 0 = 5, y 0 = 0, p x 0 = 15.…”
Section: Discussionmentioning
confidence: 99%
“…Price-Whelan et al 2016a,b;Pérez-Villegas et al 2018). Recently, Mestre et al (2020) compared the behavior of simulated streams embedded in chaotic and non-chaotic regions of the phase-space. They find that typical gravitational potentials of host galaxies can sustain chaotic orbits, which in turn do reduce the time interval during which streams can be detected.…”
Section: Analysis and Discussionmentioning
confidence: 99%